2022
DOI: 10.3390/agronomy12030647
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Root System Size and Distribution among Coffea canephora Genotypes

Abstract: This work aimed to evaluate the variability in the distribution of the root system among genotypes of C. canephora cv. Conilon and indicate management strategies for a more efficient mineral fertilization. Root distribution was evaluated in six genotypes. The experimental design was in randomized blocks with three replications. Soil monoliths measuring about 27 cm3 were collected at six different soil depths, at three row distances and nine distances of inter-row planting. The collections were carried out in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This aligns with the findings of (Schmidt et al, 2022), who reported that coffee root systems predominantly extend within 0-30 cm depth and encompass approximately 70% of the root surface area.…”
Section: Plot Characteristics Based On Coffee Root Distribution After...supporting
confidence: 91%
“…This aligns with the findings of (Schmidt et al, 2022), who reported that coffee root systems predominantly extend within 0-30 cm depth and encompass approximately 70% of the root surface area.…”
Section: Plot Characteristics Based On Coffee Root Distribution After...supporting
confidence: 91%
“…In a study on the morpho-agronomic characteristics in conilon coffee, [ 42 ] also reported the formation of groups with only one genotype. In an evaluation of the root system distribution of six conilon coffee genotypes (with a cutoff value of 92.23%), [ 43 ] observed the formation of groups with only one genotype.…”
Section: Discussionmentioning
confidence: 99%
“…RLD at the coffee stem was greater than between the coffee plants-shade tree (inter-row) (Figure 2). According to Schmidt et al (2022), coffee roots have greater root lengths near the coffee stem (up to 60 cm away from the coffee stem). This is probably because these plants are fertilized at that distance.…”
Section: Root Length Densitymentioning
confidence: 99%